2017
DOI: 10.3390/app7050527
|View full text |Cite
|
Sign up to set email alerts
|

Application of Pulsed Laser-TIG Hybrid Heat Source in Root Welding of Thick Plate Titanium Alloys

Abstract: Laser-TIG (tungsten inert gas) hybrid welding process is applied to produce stable back beads in the first layer during one-side multilayer welding. To explain why stable back beads can be formed, a comparison is conducted between single TIG and laser-TIG hybrid welding. Results indicate that during laser action the arc column is enhanced and deflected to the keyhole, which changes the spatial distribution of plasma by strong attraction. The keyhole plasma possesses extreme electric conductivity. After laser a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In the early stage, our team combined a low-power pulsed laser with a TIG arc and discovered the phenomenon of the pulsed laser attracting and compressing the arc. It has been demonstrated that this technology can improve process adaptability and achieve efficient and stable welding [18][19][20]. In addition, by changing the laser-arc malposition in the vertical welding direction, it was found that the laser could induce the arc to deflect stably and increase the width of the heat source [21].…”
Section: Introductionmentioning
confidence: 99%
“…In the early stage, our team combined a low-power pulsed laser with a TIG arc and discovered the phenomenon of the pulsed laser attracting and compressing the arc. It has been demonstrated that this technology can improve process adaptability and achieve efficient and stable welding [18][19][20]. In addition, by changing the laser-arc malposition in the vertical welding direction, it was found that the laser could induce the arc to deflect stably and increase the width of the heat source [21].…”
Section: Introductionmentioning
confidence: 99%
“…As a high-efficiency and high-quality welding technology, laser-arc hybrid welding has become a widely used welding technology [9][10][11]. Compared with a single heat source, the laser-arc hybrid heat source can effectively control the appearance of the weld seam.…”
Section: Introductionmentioning
confidence: 99%
“…Given the advantages and limitations of GMAW and LBW welding processes, HLAW (Hybrid Laser Arc Welding) processes emerge, where the action of the two heat sources in the same melting pool allows high welding characteristic in speed and penetration depth of LBW process and high geometric tolerance of the GMAW process, making it a highly productive and reproductive process [9][10][11]. In the same way, the interaction of the arc and the laser plume in a common welding pool also enables several metallurgical advantages, as formation of microstructures with less fragility due the thermal aid of the heat source generated by the electric arc acting as a cooling retarder in the fusion zone [12].…”
Section: Introductionmentioning
confidence: 99%